L-MYC gene polymorphism and risk of thyroid cancer - Yaylim-Eraltan, İ.; Bozkurt, N.; Ergen, A.; Zeybek, Ü.; Öztürk, O.; Arıkan, S.; Erbil, Y.; Uslu, İ.; Çamlıca, H.; İsbir, T. (Experimental Oncology, 2008)
L-myc gene polymorphism is a representative genetic trait responsible for an individual’s susceptibility to several cancers. However, there have been no reports concerning the association between thyroid cancer and L-myc gene polymorphism. Aim: To analyze the distribution of L-myc gene polymorphism in Turkish patients with thyroid disorders and thyroid cancers. Methods: We used a molecular genotyping method, polymerase chain reaction-based restriction fragment length polymorphism (PCR-RFLP). We studied 138 patients of whom 47 had multinodular goiter, 13 had follicular cancer and 69 had papillar cancer, in comparison with control group of 109 healthy individuals. Results: No significant difference in the distribution of genotypes was observed between thyroid patients and controls. Carrying SS or LS genotype revealed a 1.96-fold (95% CI 0.573–6.706) risk for the occurrence of follicular cancer when compared with controls, and 3.11-fold (95% CI 0.952–10.216), when compared with multinodular goiter patients (p = 0.04). Conclusion: We suggest that L-myc genotype profiling together with other susceptibility factors, may be useful in the screening for thyroid nodular malignancy.